PERENCANAAN PERSEDIAAN KOMPONEN PADA PERUSAHAAN ORIGINAL EQUIPMENT MANUFACTURER MENGGUNAKAN METODE PERSEDIAAN DETERMINISTIK DINAMIS - Erika Fatma; Intan Indriani R; Messy Fitriana (Spektrum Industri, 2019)
Determination of inventory of raw materials and components is needed to support the smoothness of the production process. Inventory management is done, in order to determine optimum inventory level, order lot size and reorder time that can minimize total inventory cost. This research applies some method in dynamic deterministic inventory model by comparing those method based on the lowest inventory total cost. This model solved basic inventory management problems, which are; the amount of goods to be ordered for each time the order made , when the order need to be made (r) and safety stock level. Based on this research, it is known that company may decrease its inventory cost by implementing suggested inventory method